Peripheral sensory neuropathy in type 2 diabetes patients: A case control study in Accra, Ghana - Yeboah, K.; Puplampu, P.; Boima, V.; Antwi, D.A.; Gyan, B.; Amoah, A.G.B. (Journal of Clinical and Translational Endocrinology, 2016)
Objective Peripheral sensory neuropathy (PSN) is a common cause of ulceration and amputation in diabetes (DM) patients. The prevalence of PSN in DM patients is largely undetermined in sub-Saharan African population. We studied the burden of PSN in DM patients using a validated questionnaire and quantitative sensory test. Methods In a case-control design, PSN was measured in 491 DM patients and 330 non-DM controls using Michigan neuropathy screening instrument (MNSI) and vibration perception threshold (VPT). PSN was defined as MNSI symptom score ≥7, MNSI examination score ≥2 or VPT ≥25V. Results The prevalence of PSN screened by MNSI symptom score, MNSI examination score and VPT was 7.1%, 51.5% and 24.5% in DM patients; and 1.5%, 24.5% and 8.5% in non-DM participants respectively. The major determinants of PSN screened by MNSI examination score were diabetes status [OR (95% CI): 4.31 (2.94–6.31), p < 0.001], age [1.03 (1.01–1.05), p < 0.001], previous [4.55 (2.11–9.82), p < 0.001] and current [8.16 (3.77–17.68), p < 0.001] smoking status. The major determinants of PSN screened by VPT were diabetes status [1.04 (1.02–1.06), p < 0.001], age [1.02 (1.01–1.03), p = 0.047], heart rate [1.78 (1.08–2.92), p = 0.023], second-hand smoking [3.66 (2.26–5.95), p < 0.001] and body height [3.28 (1.65–8.42), p = 0.015]. Conclusion Our study has shown high burden of PSN in DM patients in Ghana using simple, accurate, and non-invasive screening tools like MNSI and neurothesiometer. © 2016
Keywords: Diabetes; Ghana; Peripheral sensory neuropathy; Vibration perception threshold